Multisystem inflammatory syndrome in children related to COVID-19: Data from a Mexican national referral children's hospital - Menchaca-Aguayo, Héctor; Alpizar-Rodriguez, Deshire; Ramos-Tiñini, Pamela; Faugier-Fuentes, Enrique (Frontiers in Pediatrics, 2022)
Objectives: To describe the characteristics of patients with paediatric inflammatory multisystemic syndrome, temporally associated with SARS-CoV-2 (PIMS-TS)/ multisystem inflammatory syndrome in children (MIS-C) and to identify factors associated with admission to the paediatric intensive care unit (PICU) in Mexican children without COVID-19 vaccination. Methods: This was a cross-sectional study performed at the Hospital Infantil de Mexico Federico Gomez, a referral children’s hospital in Mexico. The study included all the cases that met criteria for PIMS-TS/MIS-C, unvaccinated, between March 2020 and January 2022. The primary outcome was the admission to PICU. The associations of PICU admission with demographic and clinical variables were estimated using logistic regression analyses. Results: We identified a total of 90 cases, with a median age of 7.5 years old, 47(52.2%) women. Previously healthy status was recorded in 76(85%) children, 68(75.6%) had positive PCR, serology test or COVID-19 exposure. PICU admission was reported in 41(45.6%) children. No reported deaths. Patients received only corticosteroids in 53.3% of cases. In univariable analyses, baseline factors associated with PICU admission were older age, hypotension or shock, positive PCR test, hypoalbuminemia, elevated procalcitonine, ferritine and lymphopenia. Age, shock at admission and hypoalbuminemia remained independently associated in the multivariable analysis adjusted by gender and previously healthy status. Conclusion: We found a high proportion of previously healthy children in patients with PIMS-TS/MIS-C in our centre. Critical care attention was received by nearly half of the children. The main treatment used were steroids. Age, shock at admission and hypoalbuminemia were factors associated with PICU admission.